2008
DOI: 10.1021/om700584m
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Optical Electron Transfer in Mixed-Valent Dinuclear Iron−Ruthenium Complexes Featuring a 1,4-Diethynylaryl Spacer

Abstract: The ground-state electronic structure and the lowest-lying excited states of the cationic mixed-valent dinuclear complexes [(η2-dppe)(η5-C5Me5)Fe[CC-1,4-(C6H4)CC]Ru(η2-dppe)2(X)][PF6] (X = Cl, 2; X = CC(4-C6H4NO2), 5) are discussed, with particular emphasis on the photoinduced intramolecular electron transfer between the ruthenium and iron centers. The location and intensities of the low-lying absorptions exhibited in the near-infrared (near-IR) range by these heterodinuclear mixed-valent (MV) complexes cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 51 publications
1
69
0
Order By: Relevance
“…[8] As previously discussed, the first oxidation at À0.23 V and the second oxidation at 0.42 V correspond to the oxidation of the Fe II and Ru II centers, respectively. The Fe III /Fe II redox potentials suggest that replacement of the chloro ligand at Ru II by the phenylethynyl and eventually the 4-nitrophenylethynyl ligand is apparently not "sensed" by the Fe II center.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…[8] As previously discussed, the first oxidation at À0.23 V and the second oxidation at 0.42 V correspond to the oxidation of the Fe II and Ru II centers, respectively. The Fe III /Fe II redox potentials suggest that replacement of the chloro ligand at Ru II by the phenylethynyl and eventually the 4-nitrophenylethynyl ligand is apparently not "sensed" by the Fe II center.…”
mentioning
confidence: 81%
“…More recently, with 2 + and the extended analogue 3-NO 2 + (Scheme 2), we demonstrated that strong electronic coupling exists in these Fe III / Ru II heterobinuclear compounds, which are new examples of nonsymmetrical mixedvalent (MV) complexes. [8] In this contribution, we report the synthesis and characterization of a new analogue (3-H) of these compounds as well as an extended hexanuclear Fe/Ru complex (4) containing three such units assembled in a C 3v fashion around a central phenyl core; the latter is a logical extension to previous studies designed to enhance the magnitude of the thirdorder NLO response (Scheme 2). We also disclose our complete results concerning the linear and nonlinear optical properties of these four redox families of heteropolynuclear compounds.…”
Section: H T U N G T R E N N U N G (H 2 -Dppe) 2 R]a C H T U N G T R mentioning
confidence: 98%
See 2 more Smart Citations
“…Due to its insensitivity to substituent effects in 1a-c, the less intense transition detected near 380 nm is attributed to the (forbidden) LF transition at the origin of the photo-ejection of one carbonyl ligand (when 2 or 1a-c are employed as photocatalysts), [1,23] while that at somewhat higher energy, near 350 nm, probably corresponds to an (allowed) dFe  *CO Following a classic approach, [37] we have therefore deconvoluted this IVCT band (A) into its Gaussian components (Figure 2b) and used eqs 3-4, 3 based on Hush theory for unsymmetrical class-II MV complexes, to derive the electronic coupling (see Supporting Information section for details). [15,3 In these equations, max, ῡmax and ῡ1/2 are the extinction coefficient, the energy of the maximum and the halfwidth of the IVCT band, respectively, while G 0 is the energy difference between the MV isomers (A and B).…”
Section: Electronic Structure Of 2[pf6]mentioning
confidence: 99%